2007
DOI: 10.1007/s10856-007-3089-3
|View full text |Cite
|
Sign up to set email alerts
|

Selective laser sintering of porous tissue engineering scaffolds from poly(l-lactide)/carbonated hydroxyapatite nanocomposite microspheres

Abstract: This study focuses on the use of bio-nanocomposite microspheres, consisting of carbonated hydroxyapatite (CHAp) nanospheres within a poly(L: -lactide) (PLLA) matrix, to produce tissue engineering (TE) scaffolds using a modified selective laser sintering (SLS) machine. PLLA microspheres and PLLA/CHAp nanocomposite microspheres were prepared by emulsion techniques. The resultant microspheres had a size range of 5-30 microm, suitable for the SLS process. Microstructural analyses revealed that the CHAp nanospheres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
117
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(121 citation statements)
references
References 18 publications
2
117
0
2
Order By: Relevance
“…Secondly, PLLA microspheres and PLLA/CHAp nanocomposite microspheres (~5-30 µm) were prepared by the oil-in-water and solid-in-oil-in-water emulsion solvent evaporation procedures respectively (Zhou, Wang et al 2007). Finally, with the modified SLS platform, prototypes of bone tissue engineering scaffolds (~10 mm) with meso-porous structure were successfully built from the PLLA microspheres and PLLA/CHAp nanocomposite microspheres (Zhou, Lee et al 2007; Zhou, Lee et al 2008). This study demonstrated a bottom-up nanotechnology approach in tissue engineering which assembling smaller scale simple biomaterials (nanoemulsion synthesized nanoscale particles, emulsion solvent evaporation prepared microscale nanocomposite spheres) into larger scale complex macro-scaffolds by laser technology.…”
Section: Wwwintechopencom Advances In Diverse Industrial Applicatiomentioning
confidence: 97%
See 1 more Smart Citation
“…Secondly, PLLA microspheres and PLLA/CHAp nanocomposite microspheres (~5-30 µm) were prepared by the oil-in-water and solid-in-oil-in-water emulsion solvent evaporation procedures respectively (Zhou, Wang et al 2007). Finally, with the modified SLS platform, prototypes of bone tissue engineering scaffolds (~10 mm) with meso-porous structure were successfully built from the PLLA microspheres and PLLA/CHAp nanocomposite microspheres (Zhou, Lee et al 2007; Zhou, Lee et al 2008). This study demonstrated a bottom-up nanotechnology approach in tissue engineering which assembling smaller scale simple biomaterials (nanoemulsion synthesized nanoscale particles, emulsion solvent evaporation prepared microscale nanocomposite spheres) into larger scale complex macro-scaffolds by laser technology.…”
Section: Wwwintechopencom Advances In Diverse Industrial Applicatiomentioning
confidence: 97%
“…The structure and properties, e.g. porosity, compression properties, in vitro degradation behavior and cytocompatibility (such as cell adhesion and growth), of these scaffolds were evaluated (Zhou, Lee et al 2008;Zhou, Wang et al 2010). The nanocomposite scaffolds provide a biomimetic environment for osteoblastic cell attachment, proliferation and differentiation and have great potential for bone tissue engineering applications (Duan, Wang et al 2010).…”
Section: Production Of 3d Porous Laser Sintered Poly(l-lactide) and Pmentioning
confidence: 99%
“…The SLS parameter settings for this PCL were optimized by Partee et al [13]. In a more recent study [14], 2D lattice structures were fabricated from PLLA/HA microspheres.…”
Section: Introductionmentioning
confidence: 99%
“…However, much of this research has only demonstrated the feasibility of fusing powder particles together, and not the fabrication of complex predesigned 3D structures. Studies which did produce complex predesigned 3D structures via SLS were those by Williams et al, Zhou et al and Partee et al [13][14][15]. Williams et al fabricated cylindrical porous scaffolds with a 3D orthogonal periodic architecture using polycaprolactone with a designed pore size of 1.75 mm.…”
Section: Introductionmentioning
confidence: 99%